Thomasclavelia ramosa and alcohol-related hepatocellular carcinoma: a microbial culturomics study - Reham Magdy Wasfy; Anissa Abdoulaye; Patrick Borentain; Babacar Mbaye; Maryam Tidjani Alou; Aurelia Caputo; Claudia Andrieu; Giovanna Mottola; Anthony Levasseur; Matthieu Million; Rene Gerolami (Gut Pathogens)
Abstract Background Gut microbiota alteration is implicated in the pathogenesis of alcoholic liver disease (ALD) and associated hepatocellular carcinoma (HCC). No study has characterized the dysbiosis associated with ALD by microbial culturomics, which certifies viability and allows pathobiont strain candidates to be characterized. Methods A case-control study (n = 59) was conducted on patients with ALD without HCC (ALD-NoHCC, n = 16), ALD with HCC (ALD-HCC, n = 19) and controls (n = 24) groups. 16 S rRNA amplicon sequencing and microbial culturomics were used as complementary methods for gut microbiome profiling. Results Compared to the control group, Thomasclavelia ramosa and Gemmiger formicilis were significantly increased in the ALD-HCC group and Mediterraneibacter gnavus was significantly increased in the ALD-NoHCC group using 16 S rRNA sequencing. By microbial culturomics, T. ramosa was detected in all ALD samples (100%), and the most enriched since cultivated in only a small proportion of controls (20%, p < 0.001). Conclusions T. ramosa, identified by culturomics and 16 rRNA sequencing, may be associated with ALD and ALD-HCC. These results highlight the potential role of T. ramosa in liver cancer, in line with its genotoxic properties and its tumor growth-promoting effect in gnotobiotic mice recently reported.